2018
DOI: 10.1038/s41598-018-28799-8
|View full text |Cite
|
Sign up to set email alerts
|

An allelic variant in the intergenic region between ERAP1 and ERAP2 correlates with an inverse expression of the two genes

Abstract: The Endoplasmatic Reticulum Aminopeptidases ERAP1 and ERAP2 are implicated in a variety of immune and non-immune functions. Most studies however have focused on their role in shaping the HLA class I peptidome by trimming peptides to the optimal size. Genome Wide Association Studies highlighted non-synonymous polymorphisms in their coding regions as associated with several immune mediated diseases. The two genes lie contiguous and oppositely oriented on the 5q15 chromosomal region. Very little is known about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 60 publications
3
31
0
Order By: Relevance
“…In a recent study a polymorphism located in the ERAP2 promoter region, rs7586269, was associated with opposite changes in the expression of ERAP1 and ERAP2, so that decreased expression of ERAP2 correlated with increased ERAP1 expression, suggesting a concerted regulation of the expression of both genes by this SNP ( 67 ). Yet, unlike rs2248374 and rs10044354, the minor allele frequency of rs7586269 is rather low in most populations.…”
Section: Erap2 Polymorphism and Expressionmentioning
confidence: 99%
“…In a recent study a polymorphism located in the ERAP2 promoter region, rs7586269, was associated with opposite changes in the expression of ERAP1 and ERAP2, so that decreased expression of ERAP2 correlated with increased ERAP1 expression, suggesting a concerted regulation of the expression of both genes by this SNP ( 67 ). Yet, unlike rs2248374 and rs10044354, the minor allele frequency of rs7586269 is rather low in most populations.…”
Section: Erap2 Polymorphism and Expressionmentioning
confidence: 99%
“…This is also suggested by the association of ERAP2 with a wider array of diseases, such as preeclampsia or IBD ( 36 38 ). At present, the relationship between ERAP1 and ERAP2 is not completely clear: there are suggestions that they can cooperate, but also that ERAP2 can regulate ERAP1 expression and activity ( 39 , 40 ), modifying the peptidome and, consequently, the expression of the HLA molecules in a subtype-dependent manner ( 23 ). LNPEP has been involved in diabetes ( 41 ) and associated with psoriasis ( 42 , 43 ), sharing the last feature with the other two aminopeptidases.…”
Section: Disease Associationsmentioning
confidence: 99%
“…A second implication is that the redundancy of their function can lead to a “quantitative” control of the three aminopeptidases so that the full expression of all of them is disfavored. In this regard, we have recently shown that the transcription of ERAP1 and ERAP2 is interlinked: the variant G at rs75862629 in the intergenic region between the two genes strongly influences the expression of the two aminopeptidases with a down-modulation of ERAP2 coupled with a significant higher expression of ERAP1 ( 40 ). Even more intriguing is the observation that the ERAP2 variants co-segregating with a lower or null expression of ERAP2 (G at rs75862629 and G at rs2248374, respectively) appear more frequent in the equatorial regions, where the malaria has been endemic.…”
Section: Do the Three Aminopeptidases Have An Extracellular Role?mentioning
confidence: 99%
“…On the other hand, individuals who are homozygous for the A-allele present about 50% more enzyme in comparison to individuals with the heterozygous haplotype, suggesting that rs2248374 may be a marker of ERAP2 protein expression. Taking this into account, this study suggests that the A-allele for this SNP may be associated with increased expression of ERAP2 in HCV chronically infected individuals, therefore affecting the antigen presentation process and leading to a greater risk of susceptibility to HCV chronicity [36]. In addition, given the role of ERAP2 as a promoter of ERAP1 activity-through the formation of heterodimers with increased trimming efficacy-it has been observed that combination of rs26618-C/rs2248374-A on the two genes also provides a greater risk of susceptibility to HCV chronicity in Han Chinese population [46].…”
Section: Eraps and Hepatitis C Virus (Hcv)mentioning
confidence: 92%
“…Another polymorphism with a considerable effect on ERAP2 protein expression is rs10044354 (C/T), where homozygosity for the C allele results in very decreased levels of ERAP2 [34,35]. Recently, a study associated the polymorphism rs75862629 (A/G) in the promoter region of the ERAP2 gene with changes in the expression of ERAP2 and ERAP1 in the Sardinian population [36]. In particular, the G allele of rs7586269 resulted in a decreased ERAP2 protein expression and a higher ERAP1 expression, suggesting the possibility of a concerted regulation of the expression of both genes by this polymorphism.…”
Section: Erap2 Genetic Variantsmentioning
confidence: 99%